University Entrepreneurship at the Service of Rural Society. The RuralYU Project as an Action Learning Process - María Begoña Sáiz Mauleón; Irene Badía Madrigal; Rita Gorriz Salanova; Inés Mondragón Pons; Victoria Olcina Marcos; Pedro Sáez Martínez; Pablo Tortosa Juanes; Guillem García Martín; María Cos Aznar (Multidisciplinary Journal for Education, Social and Technological Sciences)
The article presents the RuralYU university entrepreneurship project, developed by the Youth University Design (YUDesign) Spontaneous Generation (GE) group of the School of Design Engineering (ETSID), at the Polytechnic University of Valencia (UPV). RuralYU aspires to reduce rural depopulation in collaboration with university students, who, by carrying out academic work, cover specific needs with the aim of strengthening rural development. The idea of ​​an inter-university collaboration programme with the rural world arose after having won the Vodafone Foundation’s Project Lab 2021 national contest within the framework of GLOBAL CHANGE with the proposal “RuralLife4Good. Accommodation grant programme for the empowerment of rural environments”. The winning proposal, which was implemented as a pilot project in Ràfol de Salem during the 2021-2022 academic year, values ​​the importance of the university at the service of society, in this case as an axis of urgent and necessary activation to avoid rural abandonment.